Sexual violence as a predictor of unintended pregnancy among married women of India: evidence from the fourth round of the National Family Health Survey (2015–16) - Garg, Priyanka; Verma, Madhur; Sharma, Priyanka; Coll, Carolina V. N.; Das, Milan (BMC pregnancy and childbirth, 2022)
Background Sexual Intimate Partner Violence (IPV) is a public health problem globally, with about one in three women experiencing sexual IPV ever in their lifetime. Unintended pregnancy is one of the consequences of sexual IPV and has its repercussions that can span generations. The present study was conducted to estimate the prevalence of sexual intimate partner violence (IPV) and assess the association between sexual IPV and unintended childbirth in India among married women aged 15–49 years. Methods The National Family Health Survey-India (NFHS-4) fourth-round dataset was used for the present study. Pregnancies intention was the primary outcome variable, and the main predictor variable was self-reported sexual IPV in the past 12 months. Women’s current age, age at marriage, education and occupation, place of residence, wealth quintile, parity, religion, caste, region, mass media exposure, and husband’s education were other control variables. Weighted analysis depicted the prevalence of unintended pregnancies and their association with different socio-demographic variables. Binary logistic regression was done in two steps respecting a hierarchical approach for potential confounders. Results Approximately 6.4% of study participants had ever experienced sexual IPV in India. Prevalence of sexual IPV was significantly higher when the age of marriage was < 19 years, among uneducated, in the lowest wealth index quintile, belonging to scheduled caste, having multiparity, and not having mass media exposure. About 12.1% of pregnancies were considered unintended by the respondents, and 22.9% of women who ever had a history of sexual IPV considered the last pregnancy to be unintentional. Women who experienced sexual IPV were in younger age groups, having parity ≥1, and bigger families had significantly higher odds of having an unintended pregnancy compared to their reference groups. Conclusions We observed that sexual IPV has a significant role in unintended pregnancies. Effective counseling means should be rolled out for victims of sexual IPV as it is a taboo subject. The significant factors that can predict unintended pregnancies highlighted in our study should be acknowledged while counseling.